Tartrate stabilization of rosé wine using ion exchange resins: impact on wine sensory characteristics - Borges, Rita (2019)
Tartaric precipitation in bottled wine is an important problem for the wine industry by the undesirable aspect. Addition of certain stabilisers, such as metatartaric acid and carboxymethylcellulose (CMC), or treatment of wine with ion exchange resins, are accepted by the OIV and have been successfully used to prevent tartaric precipitation. However, there are few studies regarding rosé wine. So, the aim of this study was to evaluate the effect of cation exchange resins on rosé wine tartaric stabilisation efficiency and wine sensory quality, compared to the effect of oenological stabilisers. In this study a rosé wine from the Douro Valley Demarcated Region, 2015 vintage, was used and ion exchange resin versus different structural features, as well as metatartaric acid, were tested. The cation exchange resins process could be a useful tool to stabilise wine, as the sensory analysis data showed, since wine treatment with cation exchange resin are lesser scored for colour intensity attribute and significantly more scored for the limpidity attribute. These results show that ion exchange resins could be an interesting process for rosé wine tartaric stabilisation.